El control interno como herramienta de gestión empresarial en la administración de insumos de producción agrícola - Ramón Ruilova, Madeleyne Yaritza (2015)
Organizations and particularly small and medium enterprises (SMEs) are intended to meet its objectives in an estimated term for it must establish a pussycat of rules and standards of operation, which can be referred to the internal control system. Internal control is a process that takes place from the management who are responsible for issuing and comply with the rules that are in place, it is also an integrated and coordinated accounting and administrative controls aimed at system safeguarding integrity and equity of the company, and thus will provide better control of the assets of the organization, for better development of research a literature review where contemporary treatment of the subject matter was determined, was performed was visited place for the respective observation and thus determine the need to design a proposal that will help the management of agricultural production inputs. Business management will focus directly to growth, improving productivity and competitiveness of the company against the business world. In order to achieve efficient business management must be elements that we provide including planning, organization, communication and finally one the most essential control, it will influence directly development of family business and providing growth opportunities.